SOCIO-DEMOGRAPHIC FACTORS RESPONSIBLE FOR INTIMATE PARTNER VIOLENCE - Afra Rehman, Asiya ParveenShaikh, Hari Ram, Pardeep Kumar (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: This study was conducted among women to find out the frequency of various IPV forms and responsible socio-demographic factors. Study design. Cross sectional Setting: This study took place in gynecology OPD of PUMHS from Jan 2018 to July 2018. Patients and methods: All married women age 18-40 years presented at gynae and OBS department due to different health issues were included. Women were inquired regarding their relationships with their partners, family members, husband’ s education, residence, socioeconomic status, addiction, smoking and working status. All the data was documented in a self-designed proforma and confidentiality was maintained. Results: Total 450 women were interviewed, out of those 240 women had faced certain intimate partner violent behaviors in their life. Ol 240 rema1es, 75.339c belonged poor socioeconomic status. Psychological violence was most common among 90.839r women, physical violence was seen in 20.09e) and sexual violence was reported by 249a women. Poor socioeconomic status, low education, prolonged duration of married, female offspring; addiction was the responsible factor.s of intimate partner violence. Conclusion: It was concluded that the psychological violence most common. Low socioeconomic condition, illiteracy and addiction are the responsible .socio-demographic factors.